Laser Removal of Cosmetic Eyebrow Tattoos with a Picosecond Laser - Candice Menozzi-Smarrito; Stéphane Smarrito (MDPI AG, 2023)
This current retrospective study, including 98 patients aged 21 to 71 years, aims to assess the safety and the efficiency of a picosecond 755 nm/532 nm laser in the removal of complex eyebrows tattoos. Patients were treated with a picosecond laser at 755 nm with fluences ranging from 0.69 to 6.37 J/cm2 and at 532 nm with a fluence of 0.64 or 1.12 J/cm2. Analyses of Variance (ANOVA, single factor) and comparison tests (F-test) were conducted. A total of 70 subjects finished the full treatment. An average of three laser sessions were necessary to achieve the patients' objective (total removal, attenuation for redo, or correction). The number of sessions was significantly higher if cosmetic tattoos contained visible warm pigments (red, orange, yellow). A total of 18 patients experienced immediate grey discoloration, although this was not found to significantly influence the number of laser sessions. The main side effects were redness, swelling, and bleeding points. One patient experienced a bruise immediately after laser shots. This retrospective study has shown the picosecond laser to be safe and efficient in removing complex cosmetic tattoos. Further investigation is ongoing to assess optimal parameters for treating red and white pigments.